Effect of High-Intensity Interval Training, Moderate Continuous Training, or Guideline-Based Physical Activity on Peak Oxygen Uptake and Myocardial Fibrosis in Patients With Myocardial Infarction: Protocol for a Randomized Controlled Trial - Shi, Xiaohe; Chen, Xianyuan; Qiu, Xinfan; Luo, Wei; Luo, Xinyi; Liu, Hui; Geng, Qingshan; Ma, Huan; Xue, Ling; Guo, Lan (Frontiers in Cardiovascular Medicine, 2022)
Introduction: High Intensity Interval Training (HIIT) is an emerging method of cardiac rehabilitation, which is more and more popular in recent years. Research into the effect of HIIT on peak oxygen uptake (VO2 peak) and myocardial fibrosis among patients with myocardial infarction (MI) is lacking. Here, we describe the rationale and protocol for a clinical trial to test the following hypotheses: 1) Compared with the control group, VO2 peak will be increased in both the MICT and HIIT groups 2) Compared with the control group, myocardial fibrosis due to myocardial infarction will be improved by HIIT and MICT. Methods and analysis: This is a single-center, randomized controlled clinical trial. 180 patients with MI are to be recruited for this study. VO2 peak will be tested by cardiopulmonary exercise testing (CPET), and myocardial fibrosis will be evaluated by cardiac magnetic resonance. Other assessments include Reactive Hyperemia Index for microvascular endothelial function, microvascular obstruction, peripheral arterial tonometry or digital vasomotor response, and a series of blood and psychometric tests. Ethics and dissemination: This mechanistic clinical trial is approved by the Ethics Committee of Guangdong Provincial People’s Hospital. Findings will be disseminated through peer-reviewed publications and conference presentations. Trial registration number: NCT04863677.